Structural, electronic, magnetic, optical, thermoelectric and thermodynamic properties of R2Rh3Ge (R=Gd and Er). (April 2022) - Raïâ, M.Y.; Masrour, R.; Jabar, A.; Hamedoun, M.; Rezzouk, A.; Hourmatallah, A.; Benzakour, N.; Bouslykhane, K.; Kharbach, J.
Abstract: The structural, electronic, magnetic, optical, thermoelectric and thermodynamic properties of the Gd2 Rh3 Ge and Er2 Rh3 Ge ternary rhombohedral Laves phases compounds were studied by using the density functional theory (DFT) based the full potential linearized augmented plane wave (FPLAPW) with the generalized gradient approximation (GGA). The lattice constants of two compounds are calculated by using the Perdew–Burke–Ernzerhof (PBE)-GGA approximation. The two systems have a metallic character. Density of states as well as magnetic moment confirm that these compounds are ferromagnetic metals. The ferromagnetic state was more stable than paramagnetic state. The dielectric function, reflectivity, energy loss function, absorption coefficient and optical conductivity were calculated. The heat capacities, the thermal expansion coefficient and the Debye temperatures have also been determined from the non-equilibrium Gibbs functions. The negative value of formation energy confirms the stability of these compounds. Highlights: Magnetoelectronic, optical and thermoelectric properties of Gd(Er)2 Rh3 Ge were studied. Calculated electronic properties reveal the metallic nature for two systems. Ferromagnetic state was more stable than paramagnetic state for two systems. Thermal effects using the quasi-harmonic Debye model have been investigated. Heat capacities, expansion coefficient and Debye temperatures have been determined.